THE SIMULATION OF FLUID FLOW AT MICROELECTROMECHANICAL SYSTEM USING LATTICE BOLTZMANN EQUATION - ARMAN (NIM: 20207010), YUDHA
Several studies have been conducted to simulate the micro scale fluid flow in rarefied gas. In this regime the continuum hypothesis of Navier-Stokes equations begins to break down as the length scale of the flow domain reach the mean free path of the molecule. The distinctly different physics compared with the macro scale was the manifestations of the appearance of the slip at the contact between wall and fluid. In this research, simulation of fluid flow in Micro electromechanical system was done by using Lattice Boltzmann Equation. The geometry of the fluid flow is a cylindrical micro tube with a sphere inside as a barrier, which represents the geometry of a spinning rotor vaccum gauge system. The input profile was fluid flow with oscillating pressure with respect to time. Simulation was done at Knudsen number at 0.01 to 0.1 with assumption of Mach number < 0.3. Fluid was assumed as in viscid, Newtonian and incompressible. Each simulation was done with tangential momentum accomodation coefficient 0.7. From the simulation it is known that wall slip effect at low oscillation frequencies could increase the amplitude of the flow profile, but the magnitude velocity profile of the flow problem is greatly atenuated at large frequency of oscillating pressure gradient, from which the magnitude of the velocity profile of the flow is inversely proportional to the frequency of oscillating pressure gradient. The Knudsen number is inversely proportional to the magnitude of the velocity profile of the flow problem. The ratio between radius of the sphere and radius of the cylinder (blockage ratio) was inversely proportional to the magnitude of the instantanous velocity profile at the surface of the barrier, but it was proportional to the magnitude of the instantanous velocity profile behind barrier. The increasing of the velocity profile as the increasing of the blockage ratio is tend to the input profile magnitude of velocity profile.